AVALIAÇÃO DE MÉTODOS DE DETERMINAÇÃO DA MATÉRIA SECA DE FORRAGENS E FEZES - Demarchi, João José Assumpção de Abreu; Braun, Gilberto; Boin, Celso (REVISTA DE AGRICULTURA, 2015)
AVALIAÇÃO DE MÉTODOS DE DETERMINAÇÃO DA MATÉRIA SECA DE FORRAGENS E FEZES